2008
DOI: 10.1158/1078-0432.ccr-08-0745
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the Complement ComponentC1qACorrelates with Prolonged Response Following Rituximab Therapy of Follicular Lymphoma

Abstract: Purpose: Complement may play a role in the clinical response to rituximab and other monoclonal antibody^based therapies of cancer. The purpose of this study was to explore the relationship between the C1qA [276] polymorphism and the clinical response to rituximab in patients with follicular lymphoma. Experimental Design: Genotyping for C1qA [276A/G] was done in 133 subjects with follicular lymphoma treated with single-agent rituximab, and correlation with clinical response was done using Cox regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(92 citation statements)
references
References 52 publications
(45 reference statements)
2
89
1
Order By: Relevance
“…Similarly, several studies, although small, have implicated C1q in the emergence of SLE, as several genetic variants located in the C1q region seem to associate with this disease [18][19][20][21][22]. In addition, two small studies indicated an effect of genetic variants of C1q on the progression of cancer and the efficacy of rituximab treatment for lymphoma [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several studies, although small, have implicated C1q in the emergence of SLE, as several genetic variants located in the C1q region seem to associate with this disease [18][19][20][21][22]. In addition, two small studies indicated an effect of genetic variants of C1q on the progression of cancer and the efficacy of rituximab treatment for lymphoma [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Under our staged design, assuming a co-dominant model, a minor allele frequency of 0.44 and a joint analysis a level of 0.05, we had 97% power to detect an HR of 1.3. Power was not as good for the dominant (AG/GG vs AA) model, where we had 72% power to detect the same effect; however, power is 100% for HRs above 1.5, leaving our study more than adequately powered to detect a dominant effect similar to the one reported by Racila et al (2008). On the basis of our earlier finding that C1QA expression was associated with survival in ER-negative tumours, we stratified our sample by ER status.…”
Section: Discussionmentioning
confidence: 94%
“…There are seven single nucleotide polymorphisms (SNPs) catalogued for C1QA on the NCBI database, of which there is only one common SNP (minor allele frequency 45%) located in an exon rs172378 is a synonymous SNP characterised by a G for A substitution at position 361 (A361G). This SNP has been previously reported as being associated with breast cancer metastasis to sites linked to hematogenous spread of disease (Racila et al, 2006) and with drug response in follicular lymphoma (Racila et al, 2008). In a set of 63 patients with localised breast tumours and 38 patients with metastasis, Racila et al (2006) reported a decreased time to metastasis for G homozygote or heterozygote individuals compared with the common AA homozygote (hazard ratio, 95% CI: 2.4, 1.1 -4.1), even after adjustment for positive lymph nodes, oestrogen and progesterone receptors status.…”
mentioning
confidence: 90%
“…Clinical samples have also been used to establish correlations between the genetic makeup of the patient and response to rituximab using normal cells to study genetic polymorphisms. 15,16 Tumor samples may also be used to analyse expression profiles and establish correlations with response to mAbs. 17 …”
Section: Models Used To Understand Rituximab Cytotoxicity or Resistanmentioning
confidence: 99%
“…Homozygous A subjects achieved complete response at a higher rate than heterozygous or homozygous G subjects. 16 Tumor-related factors that are involved in resistance to rituximab include alteration in CD20 and lipids raft domain and regulation in signaling and mitochrondrial pathways (Fig. 2).…”
Section: Parameters Correlated With Rituximab Activity and Resistancementioning
confidence: 99%